2022
DOI: 10.33395/sinkron.v7i3.11488
|View full text |Cite
|
Sign up to set email alerts
|

Detection Malaria Base Microscope Digital Image with Convolutional Neural Network

Abstract: Malaria is a tropical disease that infects human red blood cells caused by infection with the plasmodium parasite. Plasmodium parasites spread to humans through female Anopheles mosquitoes and can reproduce in human blood cells. Malaria is a health problem that is at risk of causing other health problems such as anemia and even death. The current gold standard for malaria diagnosis is laboratory diagnosis by microscopic examination to find the malaria parasite through the blood cells of the patient. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Their research found that the accuracy of VGG19 is 96.86, Resnet50 is 97.29, and Inception_v3 is 97.57. Some researchers, such as Jatmika and Saputra [14], used CNN to identify rice plant diseases, Untoro and Muttaqin [15] applied CNN to detect malaria, and Sze et al [16] implemented CNN to review five-star hotels.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…Their research found that the accuracy of VGG19 is 96.86, Resnet50 is 97.29, and Inception_v3 is 97.57. Some researchers, such as Jatmika and Saputra [14], used CNN to identify rice plant diseases, Untoro and Muttaqin [15] applied CNN to detect malaria, and Sze et al [16] implemented CNN to review five-star hotels.…”
Section: Literatures Reviewmentioning
confidence: 99%